"But All Kids Yell at Their Parents, Don't They?": Social Norms About Child-to-Parent Abuse in Australia. (August 2019) - Simmons, Melanie L.; McEwan, Troy E.; Purcell, Rosemary
Child-to-parent abuse has been hampered by a lack of attention to what behaviors are commonly perceived as abusive and a poor understanding of when children's behavior stops being difficult, but normative, and becomes abusive. This study investigated what Australian parents and young people perceived as abusive behavior by children toward parents. Convenience samples of (a) parents of young people aged 14 to 25 years ( n = 201) and (b) young people aged 14 to 25 years ( n = 586) were asked to define at what frequency they believed that 40 child-to-parent behaviors became abusive. Both parents and young people perceived that children could abuse their parents, but young people were more permissive when defining abuse than were parents for behaviors involving physical aggression without injury, financial abuse, humiliation, or intimidation. The findings have implications for child-to-parent abuse measurement, particularly in relation to how coercive and verbally aggressive behavior is (or is not) defined as abusive.